Tuning Superfast Curing Thiol‐Norbornene‐Functionalized Gelatin Hydrogels for 3D Bioprinting. Issue 14 (19th June 2021) - Göckler, Tobias; Haase, Sonja; Kempter, Xenia; Pfister, Rebecca; Maciel, Bruna R.; Grimm, Alisa; Molitor, Tamara; Willenbacher, Norbert; Schepers, Ute
Abstract: Photocurable gelatin‐based hydrogels have established themselves as powerful bioinks in tissue engineering due to their excellent biocompatibility, biodegradability, light responsiveness, thermosensitivity and bioprinting properties. While gelatin methacryloyl (GelMA) has been the gold standard for many years, thiol‐ene hydrogel systems based on norbornene‐functionalized gelatin (GelNB) and a thiolated crosslinker have recently gained increasing importance. In this paper, a highly reproducible water‐based synthesis of GelNB is presented, avoiding the use of dimethyl sulfoxide (DMSO) as organic solvent and covering a broad range of degrees of functionalization (DoF: 20% to 97%). Mixing with thiolated gelatin (GelS) results in the superfast curing photoclick hydrogel GelNB/GelS. Its superior properties over GelMA, such as substantially reduced amounts of photoinitiator (0.03% (w/v)), superfast curing (1–2 s), higher network homogeneity, post‐polymerization functionalization ability, minimal cross‐reactivity with cellular components, and improved biocompatibility of hydrogel precursors and degradation products lead to increased survival of primary cells in 3D bioprinting. Post‐printing viability analysis revealed excellent survival rates of > 84% for GelNB/GelS bioinks of varying crosslinking density, while cell survival for GelMA bioinks is strongly dependent on the DoF. Hence, the semisynthetic and easily accessible GelNB/GelS hydrogel is a highly promising bioink for future medical applications and other light‐based biofabrication techniques. Abstract : Development of a highly biocompatible, superfast curing photoclick bioink, comprising norbornene‐ and thiol‐functionalized gelatin (GelNB/GelS). Thiol‐ene photocrosslinking allows a significant reduction in photoinitiator concentration while accelerating hydrogel formation upon irradiation with visible light. Combined with low toxicity of GelNB/GelS precursors and minimal cross‐reactivity, this leads to improved cell survival in extrusion‐based 3D bioprinting compared to the gold standard gelatin methacryloyl.